CRIMINAL RESPONSIBILITY PERSECUTION OF PERPETRATORS OF MOTOR VEHICLE THEFT - Anggalana Anggalana; Okta Ainita; Balgis Muhammad (Jurnal Ilmiah Advokasi, 2024)
This research explores the accountability of criminal acts of assault against motor vehicle theft offenders (Curanmor). Using both normative legal and empirical approaches, the study reveals that the causes of assault are linked to emotions, particularly after motor vehicle theft incidents. The factors contributing to criminality are categorized as internal and external. Criminological analysis indicates the roles of emotions, age, misunderstandings, and the surrounding environment in assault cases. The verdict from the Mount Sugih District Court reflects legal considerations based on the Theory of Criminal Responsibility. The judge recommends a heavier prison sentence and a larger fine as a repressive measure to deter future offenses. The government is advised to raise public awareness through legal education to prevent acts of assault. Keywords: Responsibility; Theft; Motor Vehicles